Entropy as an Existential Problem in "The Sun of the Dead" by I.S. Shmelev - Сюе, Чэнь (Philology & Human, 2020)
The purpose of the research is to highlight the problem of being and non-being in the work of I.S. Shmelev based on the material of his epic The Sun of the Dead, which rests upon the writer’s memoirs about repressions and famine in the Crimea in the early 1920s. The goal is achieved by conducting the analysis of ontological and existential units of philosophy which develop in the text through a comparison of two heroes who pass spiritual and physical tests in a social catastrophe. The will to live and the idea of entropy prevail in the work. This fact determines the novelty of the main aspect of the research. Suicide is presented as an expression of a false interpretation of a suicider’s will. The manifestation of energy is presented by the author through his attitude to things that make one’s life and construct one’s being. The conclusion about life-giving power of Christian axiology is made. Philosophical context of the story’s interpretation is based on the works of N. Abbagnano, M. Blanchot, N. Lossky, M. Montaigne, F. Nietzsche, V. Toporov and others.